27. PELANGGARAN PRINSIP NON-REFOULEMENT TERHADAP PENGUNGSI DAN PENCARI SUAKA PADA KEBIJAKAN OPERATION SOVEREIGN BORDERS SERTA IMPLIKASINYA BAGI INDONESIA SEBAGAI NEGARA TRANSIT - Anggriawan, Danang Fery; Utomo, Tri Cahyo; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
The arrival of boat people from Vietnam, Sri Lanka, and the Middle East to Australia sincethe 1970s marked the beginning of an irregular arrival in that country. Irregular arrival toAustralia in fact has an important influence for political and economic condition. In aneffort to respond these issues, the Australian government under the leadership of PrimeMinister Tony Abbott issued a policy named Operation Sovereign Borders (OSB). Themain key of the policy will be carried out by intercepting the entire Irregular MaritimeArrival (IMA) and combating the practice of people smuggling. The purpose of thisresearch is to describe the implementation of the principle of non-refoulement in theOSB’s policies that run during the reign of PM Abbott. This research showed thatAustralia had violated the principle of non-refoulement in the implementation of the policy.Australia is also suspected of committing violations of human rights of refugees andasylum seekers. While other impacts arising from the implementation of OSB’s policies isthe emergence of political tensions between Australia and Indonesia.